STIMULASI KEAKSARAAN AWAL ANAK USIA 5-6 TAHUN MELALUI MEDIA LOOSE PARTS - Maghfiroh, Shofia; Suryana, Dadan (Program Studi Pendidikan Biologi, 2024)
Based on several problems found in relevant sources regarding children's early literacy which is still in the category of starting to develop or not in accordance with the stages of reaching their developmental age. As for the early literacy of children found, children are less able to recognize vowel letter symbols, especially consonant letter symbols, children look confused when asked to connect pictures with words, not all children are able to make various forms of scribbles that have meaning, then when they trace the letters they are still upside down. , the results in bolding the letters are less neat, and when doing activities to imitate and write letters, they are still low. This research explains how to stimulate early literacy in children aged 5-6 years through loose parts media. The method used in this research is literature study. The conclusion of this research is that loose parts media can provide positive stimulation to the early literacy of children aged 5-6 years. Research results and other relevant references also found that the use of loose parts media can improve early childhood literacy.